3D spatial distribution of ore mineral phases using high resolution synchrotron micro-computed tomography (μCT) combined with optical microscopy. (June 2019) - Fatima, A.; Venkatesh, A.S.; Mukherjee, R.; Agrawal, A.K.; Singh, B.; Sarkar, P.S.; Kashyap, Y.; Shripathi, T.
Abstract: Ore minerals in dolomites and Graphite Mica Schist (GMS) were studied by synchrotron radiation micro-computed tomography (SR-μCT) and optical microscopy. High resolution μCT images of ore minerals were obtained at Imaging Beamline (BL-4), Indus-2 synchrotron radiation source for the comprehensive volume characterization of minerals. Optical microscopy was used for mineral identification, mineral/rock characterization and quantification of ore mineral assemblages was also confirmed by XRD. 3D images from SR-μCT have shown spatial distribution of major minerals and crystals of different minerals in the volume of samples. The results obtained shows that the GMS and dolomitic hosted rocks mined from region near Udaipur, Rajasthan contains sulfide mineral phases. SR-μCT facilitates visualization of the association of the various metallic minerals with the host rock. The presence of economically important metallic minerals galena, sphalerite and pyrite found in the samples through SR-μCT has implications on exploration and processing of ores. Graphical abstract: Synchrotron tomography result shows the spatial distribution of mineral phases in the Sample no. 1 (Fig a); Sample no. 2 (Fig b); Sample no. 3 (Fig c); Sample no. 4 (Fig d). Image 1 Highlights: Graphite Mica Schist (GMS) and dolomite hosted rock samples were studied with optical microscopy and synchrotron radiation based micro-computed tomography technique. The X-ray radiographs and the volume rendered images obtained with computed tomography of the samples shows the spatial distribution of the different mineral phases. The analysis of the tomographic slices was carried out for the quantification of the minerals. The results of synchrotron micro-imaging show the possibilities of utilizing this technique for characterization of mineral phases in ore minerals.